[Australian Federal Ministers for Finance and Administration ] - Abetz, Eric; Ellison, Chris, 1954-; Fahey, John, 1945-2020.; Minchin, Nick, 1953-; Slipper, Peter; Australia. Department of Finance and Administration (Canberra : Dept. of Finance and Administration, 1997)
Site contained media releases and transcripts of speeches.
Cataloguer created title (viewed on 4 Aug. 2004).
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.finance.gov.au/Ministers
System requirements: Adobe Acrobat reader for viewing PDF files.
Selected for archiving
Keywords: Abetz, Eric; Ellison, Chris, -- 1954-; Fahey, John, -- 1945-2020.; Minchin, Nick, -- 1953-; Slipper, Peter; Australia. -- Dept. of Finance and Administration -- Officials and employees; Cabinet officers -- Australia; Politicians -- Australia